THE EFFECT OF CAPITAL MARKET ON ECONOMIC GROWTH: A LITERATURE REVIEW - Jackson Yumame; Khuzaini Khuzaini (Adisam Publisher, 2025)
The capital market has a significant role in promoting economic growth through fundraising mechanisms and efficient capital allocation. This study uses the research method. The results show that a developed and liquid capital market provides cheaper and easier access to funding for firms, allowing them to expand and innovate which in turn increases productivity and production capacity. In addition, capital markets also strengthen transparency and corporate governance, which not only increases investor confidence but also maintains overall economic stability. An effective capital market encourages companies to meet higher reporting and auditing standards, which in turn improves their accountability and performance. This allows for a more efficient allocation of resources to sectors with high growth prospects, thereby spurring innovation and value addition in the economy. However, these positive impacts are more pronounced in countries with adequate financial infrastructure and supportive regulations. In developing countries, challenges such as lack of liquidity, information imbalances, and political instability remain major obstacles. In this context, the literature review emphasizes the importance of building strong capital market infrastructure, improving financial literacy, and continuous efforts in strengthening regulations to maximize the contribution of capital markets to economic growth. With the right strategy, capital markets can be an important pillar in promoting sustainable and inclusive economic growth.